Good Intentions - Colaianni, C. Alessandra (Ars Medica, 2019)
Short-term global health engagements are widespread and appealing to medical students for many reasons: exposure to healthcare in low-resource settings, opportunities to travel and meet medical students from a different country, opportunities for research and volunteerism. However, they raise significant ethical questions: how much training should students have before embarking on these trips, and what should students be allowed to do? With these questions in mind, the author reflects on her own experience as a first-year medical student on a volunteer trip to Montero, Bolivia.